Understanding neutrophil development and function in health and disease - Kwok, Immanuel Weng Han (Nanyang Technological University, 2020)
Neutrophils are specialised innate cells that require constant replenishment from proliferative bone marrow (BM) precursors due to their short half-life. While it is established that neutrophils are derived from the granulocyte-macrophage progenitor (GMP), the differentiation pathways from GMP to functional mature neutrophils are poorly defined. Utilising several high-dimensional cytometric, transcriptomic and computational analyses, we characterised each neutrophil developmental stage and investigated their unique phenotypical and functional properties. Here, we present the identification of two distinct proliferative and committed neutrophil progenitors (proNeu1 and proNeu2) that give rise to a neutrophil precursor (preNeus), which sequentially differentiates into immature neutrophils and mature neutrophils. We showed the transcriptional programming of neutrophil commitment and maturation, as each subset progressively substitute their proliferative program and gain migratory and effector functions. Notably, the transcription factor C/EBPe was critical for development, not only in governing the neutrophil lineage fate but also for the generation of preNeus. In summary, our study identifies specialised granulocytic populations in the BM that ensure supply under homeostasis and stress responses. We envision that these findings will help to unravel the complexity of neutrophil heterogeneity in both health disease conditions.